PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN TOKO NORDTIME 39 KINIBALU - Eka Trisnawati; Subijanto Subijanto (Jurnal Ekonomi, Bisnis dan Social, 2023)
Analysis of the Effect of Product Quality, Quality Service and Customer Value to This study aims to examine and analyze the influence of quality Products, service quality and customer value to customer satisfaction. Sampling techniques used in this study probability techniques sampling and samples used as many as 100 respondents. Data analysis is done by using statistical tools SPSS version 26. Based on the results of data analysis using known t test that product quality has a positive and significant effect on satisfaction customers, the quality of Service has a positive effect but does not affect significant to customer satisfaction and positive influence customer value and significant to customer satisfaction. Product quality, service quality and customer value simultaneously affects customer satisfaction.